Clinical and economic analysis of biologic drugs in treatment of psoriasis - A. A. Kubanov; S. K. Zyryanov; D. Yu. Belousov (Качественная клиническая практика, 2018)
Purpose. To evaluate the cost effectiveness of use of ustekinumab (Stelara®), infliximab (Remicade®) and adalimumab (Humira®) for treatment of moderate and severe psoriasis. Methods. A cost-effectiveness analysis and budget impact analysis have been conducted. Clinical efficacy was evaluated by reduction in PASI scores by 50, 75 and 90%. The efficacy and safety of compared anti-psoriasis agents were derived from a meta-analysis of efficacy of biologic agents in treatment of moderate and severe plague psoriasis containing all compared drugs. The expenses counted includes costs of anti-psoriasis therapy, cost of drug administration and associated medical services. Results. Ustekinumab (Stelara®) was shown to be the most cost-effective biologic agent with respect to the cost per patient achieving PASI50, PASI75 and PASI90 scores. Total direct medical costs associated with use of ustekinumab for treatment of psoriasis turned to be 2 824 rub. (0.2%) per patient per year less than total cost of treatment associated with adalimumab and 444 315 rub. (27.3%) per patient per year less than total costs associated with infliximab. Thus, treatment of patient with moderate and severe psoriasis with ustekinumab results in optimal health care resource utilization. Conclusion. Prescribing of ustekinumab (Stelara®) was demonstrated to be dominating strategy of treatment of moderate and severe psoriasis being the most effective and less costly strategy among those based on other biologic agents.